Reconsidering the performance of DEVS modeling and simulation environments using the DEVStone benchmark. (June 2017) - Risco-Martín, José L.; Mittal, Saurabh; Fabero Jiménez, Juan Carlos; Zapater, Marina; Hermida Correa, Román
The discrete event system specification formalism, which supports hierarchical and modular model composition, has been widely used to understand, analyze and develop a variety of systems. Discrete event system specification has been implemented in various languages and platforms over the years. The DEVStone benchmark was conceived to generate a set of models with varied structure and behavior, and to automate the evaluation of the performance of discrete event system specification-based simulators. However, DEVStone is still in a preliminary phase and more model analysis is required. In this paper, we revisit DEVStone introducing new equations to compute the number of events triggered. We also introduce a new benchmark with a similar central processing unit and memory requirements to the most complex benchmark in DEVStone, but with an easier implementation and with it being more manageable analytically. Finally, we compare both the performance and memory footprint of five different discrete event system specification simulators in two different hardware platforms.